2017
DOI: 10.1371/journal.pone.0187254
|View full text |Cite
|
Sign up to set email alerts
|

Increased engagement of the cognitive control network associated with music training in children during an fMRI Stroop task

Abstract: Playing a musical instrument engages various sensorimotor processes and draws on cognitive capacities collectively termed executive functions. However, while music training is believed to associated with enhancements in certain cognitive and language abilities, studies that have explored the specific relationship between music and executive function have yielded conflicting results. As part of an ongoing longitudinal study, we investigated the effects of music training on executive function using fMRI and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 118 publications
(132 reference statements)
5
97
2
7
Order By: Relevance
“…Overall, longitudinal studies have demonstrated structural changes following musical training, and one question of great interest to the field has been whether these changes may transfer to nonmusical skill development as well. Neuroimaging findings support the notion that musical training induces neuroplasticity in several brain regions and networks known to be involved in cognitive/perceptual processing, in domains such as speech, language, reading, and higher order cognitive processing . Numerous longitudinal studies investigating behavior and corresponding brain function have suggested that musical training may support certain aspects of academic achievement .…”
Section: Training‐induced Structural Plasticity In Musicianssupporting
confidence: 63%
“…Overall, longitudinal studies have demonstrated structural changes following musical training, and one question of great interest to the field has been whether these changes may transfer to nonmusical skill development as well. Neuroimaging findings support the notion that musical training induces neuroplasticity in several brain regions and networks known to be involved in cognitive/perceptual processing, in domains such as speech, language, reading, and higher order cognitive processing . Numerous longitudinal studies investigating behavior and corresponding brain function have suggested that musical training may support certain aspects of academic achievement .…”
Section: Training‐induced Structural Plasticity In Musicianssupporting
confidence: 63%
“…No comparable significant difference was observed when the children with music training were compared with the children with sports training. Percent signal change in both the inferior frontal gyrus and the supplementary motor area was positively correlated with performance on a behavioral version of the color-word Stroop task that was completed outside of the scanner 43 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Individual subject‐level models were then combined into a higher level to compare differences in brain activation during these contrasting conditions between the three groups. Percent change of the BOLD signal between the incongruent and congruent conditions within two ROIs, the inferior frontal gyrus and the supplementary motor area, was then correlated with behavioral measures collected outside of the scanner during tasks of cognitive control …”
Section: Methodsmentioning
confidence: 99%
“…In children, one study found that 9‐ to 12‐year‐old musically trained children recruited the supplemental motor area and ventrolateral prefrontal cortex more strongly than untrained children in an audiovisual set‐shifting task . Along the same lines, a subsequent study focused on inhibition found that school‐aged children who had participated in a music training program for 2 years showed stronger activation in the ACC, inferior frontal gyrus, pre‐supplementary motor area (SMA)/SMA, and insula on the incongruent trials of a color–word Stroop task relative to an active control group participating in a sports training and a passive control group who did not participate in an extracurricular program …”
Section: Previous Studies On Musical Training and The Neural Correlatmentioning
confidence: 96%
“…22 Along the same lines, a subsequent study focused on inhibition found that school-aged children who had participated in a music training program for 2 years showed stronger activation in the ACC, inferior frontal gyrus, pre-supplementary motor area (SMA)/SMA, and insula on the incongruent trials of a color-word Stroop task relative to an active control group participating in a sports training and a passive control group who did not participate in an extracurricular program. 72 It is not possible to draw definite conclusions about the neural basis of the supposed musician advantage in executive functions based on such a scarce literature, especially since these studies have targeted different (albeit related) executive functions. Nonetheless, these studies tentatively suggest that adult musicians show decreased activity in more anterior prefrontal regions, while musically trained children display increased activity in more posterior frontal cortex (as indicated by the peak voxel coordinates) and other structures during executive function tasks.…”
Section: Previous Studies On Musical Training and The Neural Correlatmentioning
confidence: 99%